Board independence, corruption and innovation: some evidence on UK subsidiaries - Sena, Vania; Duygun, Meryem; Lubrano, Guiseppe; Marra, Marianna; Shaban, Mohamed (Elsevier, 2018)
In this paper we test the hypothesis that independent boards can insulate a company from the detrimental impact of corruption on its performance (proxied by innovation). To this purpose, we have estimated an innovation production function that links innovation outputs to innovation input (namely investment in R&D) on a sample of manufacturing subsidiaries controlled by British multinationals and located in 30 countries. Our analysis covers the period 2005¬‐2013. After controlling for the subsidiary’s characteristics (including the ownership structure and whether the main shareholders are from Common Law countries), we find that independent boards may mitigate the negative impact of corruption on innovation as subsidiaries located in more corrupt countries and with more independent boards tend to invest more in R&D and register more valuable patents. These results still hold after controlling for the average age of the directors, the proportion of directors with no local business affiliations and government effectiveness.